„Latine loquor!” – czyli „żywa łacina” jako metoda dydaktyczna (Latine loquor! – Living Latin as a teaching method) - Loch, Marcin (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2016)
This article discusses the various problems one faces as a teacher of Latin in Poland. These problems are partly due to the permanently decreasing number of Latin lessons in schools. This decrease, however, has not been considered by those responsible for the core curriculum, which is now too extensive and does not match the amount of time provided for Latin classes. The lack of reform in the didactics of Latin also takes its toll (namely the continuous usage of the grammar-translation method). Direct methods, which include dr. Rouse’s method, Ørberg’s method and Assimil method (all discussed briefly in this article) could prove to be a useful solution to these problems.